Demokrasi Deliberatif dan Problematika dalam Proses Penunjukan Penjabat (PJ) Kepala Daerah Aceh Tahun 2022 - Rizki, Makbull; Solihah, Ratnia; Rizkiyansyah, Ferry Kurnia; Rantona, Safutra (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2025)
The application of simultaneous regional elections in 2024 has presented several implications for the changing political landscape in Indonesia, including in provincial areas such as Aceh. Different from other areas, the pros and cons of appointing an acting regional head in Aceh seem to lack consensus or approval from the local government regarding the postponement of regional elections in 2022 based on autonomy value in Aceh. The central government of Indonesia and the Aceh government are involved in this issue. This situation has both pros and cons for all elements of society. Therefore, this issue has become the focus of this research. To achieve this, researchers employ a qualitative research method, including in-depth interviews, and collect relevant literature related to the topic. This research is expected to provide a specific depiction of the mechanisms involved in appointing an acting regional head, the problems encountered, and the democratic aspects of the appointment process. Keywords: Deliberative Democracy, Appointment of Acting Regional Head (PJ), Problems of Acting Appointment, Aceh Province.